Interspecies Comparative Analyses Reveal Distinct Carbohydrate-Responsive Systems among Drosophila Species - Watanabe, Kaori; Kanaoka, Yasutetsu; Mizutani, Shoko; Uchiyama, Hironobu; Yajima, Shunsuke; Watada, Masayoshi; Uemura, Tadashi; Hattori, Yukako (Cell reports (Cambridge), 2019)
During evolution, organisms have acquired variable feeding habits. Some species are nutritional generalists that adapt to various food resources, while others are specialists, feeding on specific resources. However, much remains to be discovered about how generalists adapt to diversified diets. We find that larvae of the generalists Drosophila melanogaster and D. simulans develop on three diets with different nutrient balances, whereas specialists D. sechellia and D. elegans cannot develop on carbohydrate-rich diets. The generalist D. melanogaster downregulates the expression of diverse metabolic genes systemically by transforming growth factor β (TGF-β)/Activin signaling, maintains metabolic homeostasis, and successfully adapts to the diets. In contrast, the specialist D. sechellia expresses those metabolic genes at higher levels and accumulates various metabolites on the carbohydrate-rich diet, culminating in reduced adaptation. Phenotypic similarities and differences strongly suggest that the robust carbohydrate-responsive regulatory systems are evolutionarily retained through genome-environment interactions in the generalists and contribute to their nutritional adaptabilities. [Display omitted] •The generalists adapt to various nutrient balances, whereas the specialists cannot•The generalists regulate carbohydrate-responsive gene expression by Activin signaling•The specialist species are defective in carbohydrate-responsive gene regulation•The specialist D. sechellia accumulates various metabolites and reduces adaptation Watanabe et al. uncover robust carbohydrate-responsive regulatory systems, including TGF-β/Activin signaling, which allow larvae of a generalist Drosophila melanogaster to adapt to various nutrient balances. In contrast, a specialist D. sechellia is defective in the systems and no longer maintains metabolic homeostasis, culminating in reduced adaptation to carbohydrate-rich diets.